2014
DOI: 10.1371/journal.pone.0105713
|View full text |Cite
|
Sign up to set email alerts
|

TLR Ligands Induce Antiviral Responses in Chicken Macrophages

Abstract: Chicken macrophages express several receptors for recognition of pathogens, including Toll-like receptors (TLRs). TLRs bind to pathogen-associated molecular patterns (PAMPs) derived from bacterial or viral pathogens leading to the activation of macrophages. Macrophages play a critical role in immunity against viruses, including influenza viruses. The present study was designed to test the hypothesis that treatment of chicken macrophages with TLR ligands reduces avian influenza replication. Furthermore, we soug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
74
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 63 publications
(67 reference statements)
10
74
1
Order By: Relevance
“…CpG with different motifs have distinct immunomodulatory effects [10,16,25]. In chickens, most studies have focused on class B CpG, such as 2007 and 1826 [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CpG with different motifs have distinct immunomodulatory effects [10,16,25]. In chickens, most studies have focused on class B CpG, such as 2007 and 1826 [3].…”
Section: Discussionmentioning
confidence: 99%
“…TLR ligands can be employed as stand-alone antibacterial or antiviral agents. For example, TLR2, 4 and 21 ligands significantly reduce replication of AIV in chicken macrophages [16]. TLR2 and 9 ligands protect mice against lethal influenza virus infection [11], and TLR2, 3, 4, 21 ligands protect against bacterial and viral infections [3].…”
Section: Q2mentioning
confidence: 99%
See 1 more Smart Citation
“…For example in chickens, the direct interaction of TLR4 and TLR2 with microbial LPS and lipoprotein, respectively, triggers expression of pro-inflammatory cytokines by heterophils (Kogut et al, 2005;Malek et al, 2004), macrophages (St. Paul et al, 2013a;Barjesteh et al, 2014), splenocytes (St. Paul et al, 2011) and cells of the bursa of Fabricius (St. Paul et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…Chickens, however, do not express TLR9, but TLR21 binds DNA with similar affinity and specificity (Brownlie et al, 2009). Previous results have shown that class B CpG oligodeoxynucleotides (ODN) promote the up-regulation of interferon (IFN)-␥ and IL-10 in the bursa of Fabricius (St. Paul et al, 2012b), IFN-␥, IFN-␤, IL-1␤, and interferon regulatory factor (IFR) 7 in chicken macrophages (Barjesteh et al, 2014), IFN-␥, major histocompatibility complex (MHC)-II, and IL-10 in chicken splenocytes (St. Paul et al, 2011), IL-1␤, IL-6 and CxCLi2 in chicken thrombocytes (St. Paul et al, 2012a) and type I IFNs in chicken erythrocytes (St. Paul et al, 2013c).…”
Section: Introductionmentioning
confidence: 99%